Blue Organic-Inorganic Light Emitting Diode Based on Electroluminescence CdS Nanoparticle - Naje, Asama N.; Ibrahim , Omar A.; Abdullah, Estabraq T. (Iraqi Journal of Science, 2023)
A hybrid cadmium sulfide nanoparticles (CdSNPs) electroluminescence (EL) device was fabricated by Phase – Segregated Method and characterized. It was fabricated as layers of (ITO/poly-TPD:CdS ) and (ITO/poly-TPD:CdS /Alq3). Poly-TPD is an excellent Hole Transport Layer (HTL), CdSNPs is an emitting layer and Alq3 as electron transport layer (ETL). The EL of Organic-Inorganic Light Emitting Diode (OILED) was studied at room temperature at 26V. This was achieved according to band-to-band transition in CdSNPs. From the I-V curve behavior, the addition of Alq3 layer decreased the transfer of electrons by about 250 times. The I-V behavior for (poly-TPD/CdS) is exponential with a maximum current of 4500 µA. While, the current is constant for (poly-TPD:CdS /Alq3) and the maximum current was 16.5 µA. Semiconductor nanoparticles like CdS are attractive for fabricating hybrid LEDs with spectrally pure color, low operating voltage values, and short-wavelength electro-luminescence, needed for the RGB devices. The correlated color temperature (CCT) was equal to (1700 oK) for the emitted blue light.